Successful treatment of peripartum cardiomyopathy: a case report - N. V. Korneeva; N. N. Mislimova (Кардиоваскулярная терапия и профилактика)
Peripartum cardiomyopathy is a rare disease that occurs in late pregnancy and early postpartum, manifesting as rapidly progressive heart failure. To save the mother’s life, quick diagnosis, correct routing and pathogenetic treatment is required. The demonstrated case shows a detailed childbirth situation, which could provoke peripartum cardiomyopathy in a 36-year-old woman with subclinical hypothyroidism, rapid recognition of the clinical situation with the correct treatment tactics, which helped not only to stabilize the patient’s condition, but also to completely restore the left ventricular contractile function. Practitioners are interested in following the tactics of drug treatment in the intensive care unit and further at the outpatient stage using a specific clinical example.